Pinocchio [videorecording (DVD)] - Collodi, Carlo, 1826-1890 (Walt Disney signature collection., 2017)
Woodcarver Geppetto has pets Figaro the cat and Cleo the fish. He has just made a little wooden puppet called Pinocchio. Wishing upon a star before he goes to bed, Geppetto wishes that Pinocchio would become a real boy. As Geppetto sleeps, the Blue Fairy arrives and partially grants his wish. Pinocchio can come to life, but he must prove himself worthy before becoming a real boy. He will require some guidance, and Jiminy Cricket agrees to act as his conscience. After some unfortunate incidents, Pinocchio finds himself in trouble. The Blue Fairy appears. Pinocchio lies to her and his nose grows. He is forgiven, but warned not to lie again.